Systems thinking applied to municipal solid waste management: A case study of Italy - Miranda, Sophia de Assis Bombardelli (2024)
Municipal solid waste management is a complex issue that can be described as a ‘wicked problem’, due to the interconnections of environmental, economic, technological and social aspects. Simple solutions that don’t address the complexity of the system remain a significant hurdle in the development of sustainable waste management. This study aims at identifying and understanding the problem of municipal solid waste management through a system thinking perspective and addresses the role of collaboration in its management. It identifies the main processes and dynamics within waste management and how these interactions affect collaboration efforts. Italy is used as a case study, where stakeholders that represent the system are interviewed and the data is analysed through coding from a system thinking perspective. The findings suggest that systems thinking is effective in creating a comprehensive understanding of a complex problem such as waste management. By mapping out its flows, stocks, variables and complex dynamics, system thinking offers a clearer picture of the ‘wicked problem’, highlighting potential solutions, such as multilevel governance approaches and systemic collaboration. These insights offer long term solutions to the complex problem of waste management, not only for Italy but for other nations pursuing Circular Economy and sustainable development goals.